Ecosistema y explosión de las fuentes en la sociedad datacéntrica: nuevos materiales para la investigación cultural. Análisis del sistema expositivo español como estudio de caso - Rodríguez-Ortega, Nuria (Editorial de la Universidad de Cantabria, 2018)
An ecosystem of heterogeneous, mass-scale sources that are globally distributed, together the transition to a new knowledge economy based on the value of data, define the epistemological paradigms that are of our times. Given this new scenario, the purpose of this essay is to explore, through specific examples taken from the Exhibitium Project, how to face the double challenge of accessing to this new ecosystem of sources and transforming their content into reusable data for cultural interpretation.
Keywords: Arte - Historia - Congresos; Digital art history; Digital humanities; Art exhibitions; Research infrastructures; Data analysis; Network analysis